Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Substituting x = – 3 in x^2 + 5x + 4 gives (– 3)^2 +5(– 3)+4 = 9+2+4 = 15

Substituting x = – 3 in
 x^2 + 5x + 4 gives (– 3)^2 +5(– 3)+4 = 9+2+4 = 15

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5965 Points
10 months ago
Dear Student

Substituting x =–3 in x^2+5x+4, we have
x^2+5x+4 = (–3)^2+5(–3)+4 = 9–15+4 = - 2.
This is the correct answer.

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free